Winning conditions how to achieve the professional success you deserve by managing the details that matter - Hofbeck, Christine (Tantor Media, 2020)
Let's face it-professional success isn't built only on the work itself. Instead, it's often largely influenced by the manner in which you share or present your work. Small improvements in delivery can result in substantial improvements in outcome.People succeed not simply because they deliver a winning work product or idea, but also because they deliver their work or idea in a winning way.Winning Conditions is a joyful, insightful, and empowering book about delivering your work and ideas so that they (and you!) are more likely to be recognized, accepted, and celebrated. By consciously implementing these ideas, you'll see your colleagues and customers respond more positively to you and your great work. Your strong reputation and overall success will grow. You will begin to win.With Winning Conditions, you can show the world what you're capable of-it's probably more than you ever thought possible.
Downloadable audio file
Keywords: Success -- Psychological aspects; Success in business; Succès; Aspect psychologique; Succès dans les affaires; BUSINESS & ECONOMICS / Personal Success; Business; Downloadable audio books; Audiobooks; Livres audio